Partnering to create a core communication board to improve theater experiences - Tucker, Lauren (Assistive Technology Outcomes and Benefits, 2021)
This article outlines a partnership between a nonprofit theater in Connecticut and pre-service special education teachers at a local university. The goal of the collaboration was to increase the accessibility of the sensory-friendly performances and events designed for students in PK-12. The process of creating visual supports and a core communication board is shared, in addition to the designing of training and implementation phases. The project not only resulted in improved supports for the school-aged sensory-friendly events for the next season, but also in a demonstrable perspective shift on the importance of inclusivity and community communication supports among pre-service teachers and community members. © 2021, Assistive Technology Industry Association. All rights reserved.
Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85114899160
Keywords: dept.sed; peer-reviewed; ⛔ No DOI found